Disruption of the NlpD lipoprotein of the plague pathogen Yersinia pestis affects iron acquisition and the activity of the twin-arginine translocation system. - Avital Tidhar; Yinon Levy; Ayelet Zauberman; Yaron Vagima; David Gur; Moshe Aftalion; Ofir Israeli; Theodor Chitlaru; Naomi Ariel; Yehuda Flashner; Anat Zvi; Emanuelle Mamroud (Public Library of Science (PLoS), 2019)
We have previously shown that the cell morphogenesis NlpD lipoprotein is essential for virulence of the plague bacteria, Yersinia pestis. To elucidate the role of NlpD in Y. pestis pathogenicity, we conducted a whole-genome comparative transcriptome analysis of the wild-type Y. pestis strain and an nlpD mutant under conditions mimicking early stages of infection. The analysis suggested that NlpD is involved in three phenomena: (i) Envelope stability/integrity evidenced by compensatory up-regulation of the Cpx and Psp membrane stress-response systems in the mutant; (ii) iron acquisition, supported by modulation of iron metabolism genes and by limited growth in iron-deprived medium; (iii) activity of the twin-arginine (Tat) system, which translocates folded proteins across the cytoplasmic membrane. Virulence studies of Y. pestis strains mutated in individual Tat components clearly indicated that the Tat system is central in Y. pestis pathogenicity and substantiated the assumption that NlpD essentiality in iron utilization involves the activity of the Tat system. This study reveals a new role for NlpD in Tat system activity and iron assimilation suggesting a modality by which this lipoprotein is involved in Y. pestis pathogenesis.